The Impact of the Discovery Learning Model on Learning Outcomes in Basic Chemistry at SMAN 1 Sungayang - Widia Rahmanda; Elvy Rahmi Mawarnis; Dwivelia Aftika Sari (Universitas Pendidikan Mandalika, 2026)
This study explores the effect of the Discovery Learning model on student learning outcomes in basic chemistry at SMAN 1 Sungayang. This is a quantitative study with a quasi-experimental design in the form of a nonequivalent control group. The study population consisted of all 10th-grade students, with a sample of two classes selected through purposive sampling. The experimental group used the Discovery Learning model, while the control group received conventional instruction. Data analysis included tests of normality and homogeneity, followed by hypothesis testing. The results indicate that the Discovery Learning model significantly improves student learning outcomes, demonstrating its effectiveness in promoting active engagement and a deeper understanding of chemical concepts. Thus, this model can be used as an alternative in chemistry instruction to improve the quality of student learning outcomes.